2022
DOI: 10.1128/spectrum.01478-22
|View full text |Cite
|
Sign up to set email alerts
|

BET-Independent Murine Leukemia Virus Integration Is Retargeted In Vivo and Selects Distinct Genomic Elements for Lymphomagenesis

Abstract: In this study, we have shown that the in vivo replication of murine leukemia virus happens independently of BET proteins, which are key host determinants involved in retroviral integration site selection. This finding opens a new research line in the discovery of alternative viral or host factors that may complement the dominant host factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Ashkar et al showed that the introduction of W390A in MLV IN resulted in an MLV vector characterized by an altered integration pattern in cell culture but produced at similar titers as the WT MLV [ 54 ]. Next, Nombela et al inserted W390A as a single point mutation in the viral IN of the MLV molecular clone p63.2 [ 55 ]. By comparing wild–type (WT) MLV with BET–independent (Bin) W390A MLV replication, the role of BET proteins in MLV replication, integration and tumorigenesis was studied in vivo.…”
Section: Molecular Mechanisms Underlying MLV Integrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Ashkar et al showed that the introduction of W390A in MLV IN resulted in an MLV vector characterized by an altered integration pattern in cell culture but produced at similar titers as the WT MLV [ 54 ]. Next, Nombela et al inserted W390A as a single point mutation in the viral IN of the MLV molecular clone p63.2 [ 55 ]. By comparing wild–type (WT) MLV with BET–independent (Bin) W390A MLV replication, the role of BET proteins in MLV replication, integration and tumorigenesis was studied in vivo.…”
Section: Molecular Mechanisms Underlying MLV Integrationmentioning
confidence: 99%
“…The W390 mutation induced the retargeting of integration away from CpG islands, DNase I–hypersensitive sites, GC–enriched regions, TSSs and enhancers. Uncoupling MLV integration from BET proteins resulted in increased integration in proximity to histone marks linked with active transcription, such as H3K36me3 [ 55 ]. Next, the effect of the W390A mutation on MLV leukemogenesis in the blood, spleen and thymus was assessed.…”
Section: Molecular Mechanisms Underlying MLV Integrationmentioning
confidence: 99%
See 3 more Smart Citations